Durius e Leça : dois percursos de um mesmo itinerário – problemáticas em torno das ânforas Haltern 70 - Morais, Rui (Portvgalia : Revista de Arqueologia do Departamento de Ciências e Técnicas do Património da FLUP, 2018)
The study of the amphorae found in an excavation in the city of Porto (Aljube) and in the hill fort of Monte Castêlo (Castro de Guifões), in Matosinhos, allows us to make some observations on two important coastal nuclei in the Peninsular Northwest. In Roman times these nuclei, situated in the banks of the Douro and Leça Rivers, acquired a privileged status in the context of the Atlantic navigation and in the transport and redistribution of goods at a local and regional level. In this perspective, the study of the amphorae proved to be very interesting because the ones found in Aljube matched a landfill of material dated from the change of the Era while the ones found in Monte Castêlo came from a settlement with a long diachronic occupation throughout all the Imperial period. Moreover, they have an interesting fact in common: they hold one of the largest quantities of Haltern 70 amphorae documented so far in places on consumption. Throughout this study we will put forward the possibility that a hybrid system of market might have existed in Roman times. This system would have been related to the trade of Haltern 70 amphorae and would have been based on a close relationship between the variables costs of transportation/ ethnicity of the populations.